Respuesta :
Answer:
1
Step-by-step explanation:
First plug in x and y:
(3)^2 - 2(3)(2) + (2)^2
Use order of operations (PEMDAS). First, evaluate the exponents:
9 - 2(3)(2) + 4
Then multiplication:
9 - 12 + 4
Then addition and subtraction, which is done from left to right:
-3 + 4
1
Answer:
[tex] {x}^{2} - 2xy + {y}^{2} \\ x = 3 \\ y = 2 \\ then \: we \: can \: written \: as \\ {3}^{2} - 2 \times 3 \times 2 + {2}^{2} \\ = 9 - 12 + 4 \\ = - 3 + 4 \\ = 1 \\ or \: in \: another \: way \\ this \: is \: the \: expansion \: of \: {(x - y)}^{2} \\ so \: put \: x = 3and \: = 2in {(x - y)}^{2} \\ then \: {(3 - 2)}^{2} \\ = {1}^{2} = 1 \\ thank \: you[/tex]